Fear of terrorism and its correlates in young men and women from the United States and South Korea. Issue 1 (29th January 2020) - Hong, Fang; Lin, Yijing; Jang, Mikyung; Tarullo, Amanda; Ashy, Majed; Malley-Morrison, Kathleen
Abstract : Purpose: The purpose of this study was to examine associations between fear of terrorism and several predictors (gender and nationality) and outcomes (moral disengagement, authoritarianism, aggression and social anxiety) in the USA and South Korean young adults. Of particular interest were the potential moderating and mediating roles of moral disengagement between fear of terrorism and the other outcomes. Design/methodology/approach: Samples of 251 college students from the USA and 211 college students from South Korea completed survey packets including measures of fear of terrorism, moral disengagement, authoritarianism, aggression and social anxiety. Findings: US participants expressed greater concern about a terrorist threat to their country, while South Koreans worried more about terrorist threats to their family or themselves. Females in both countries reported greater fear of terrorism and social anxiety. In both countries, fear of terrorism was associated with aggression, social anxiety and moral disengagement. Mediation analyses showed that fear of terrorism exerted a significant direct effect and an indirect effect via moral disengagement on aggression and authoritarianism in the US sample. Moderation analyses revealed that moral disengagement moderated the relationship between fear of terrorism and social anxiety in the Korean sample. Research limitations/implications: This study has the common limitations of cross-sectional studies; i.e. it cannot prove causal relationships. Practical implications: The findings support Albert Bandura's view that efforts to address the excesses of counterterrorism and other negative outcomes of fear of terrorism, attending to issues of moral disengagement may be helpful. Originality/value: The authors findings provide support for the view that fear of terrorism is associated with negative psychological and social outcomes and that moral disengagement can play an important role in those negative outcomes. Moreover, it adds to evidence that the negative role of moral disengagement shows considerable generalizability across gender and two very different cultures.